R&D Incentives and Market Structure: A Dynamic Analysis - Roberto Cellini; Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2004)
We investigate dynamic R&D for process innovation in an oligopoly where firms invest in cost-reducing activities. We focus on the relationship between R&D intensity and market structure, proving that the industry R&D investment monotonically increases in the number of firms. This Arrowian result contradicts the established wisdom acquired from static games on the same topic.
Keywords: 330; Forschung; Technischer Fortschritt; Marktstruktur; Oligopol; Spillover-Effekt; Dynamisches Spiel; Theorie